Construction of the Phylogenetic Tree from Genus of Carnivorous Plants Based on Internal Transcribed Spacer (ITS) Marker in Silico - Fahmi Azrial (Indonesian Journal of Biology Education, 2025)
Carnivorous plants are plants that have morphological adaptations to prey on and digest small animals as an additional source of nutrition. There are several genera of carnivorous plants, namely Nepenthes, Drosera, Heliamphora, and Pinguicula. Among these genera, they have similar morphological and molecular characteristics and uniqueness. Molecular characterization needs to be carried out to analyze the genetic relationships between carnivorous plant species through the construction of phylogenetic trees. This study aims to obtain information on genetic relationships in several genera of carnivorous plants using an in silico phylogenetic tree based on Internal Transcribed Spacer (ITS) sequences. ITS sequences were collected from NCBI by searching for species names and then aligned using Clustal-W. Subsequently, the construction of the phylogenetic tree was performed using MEGA X with the Maximum Likelihood method and Bootstrap analysis of 1000. The results of the phylogenetic construction of several carnivorous plant genera are divided into two main clades. Clade I is divided into sub-clades: clade IA consists of species from the genera Heliamphora and Drosera with a bootstrap value of 76, while clade IB consists of species from the genus Pinguicula and one species from Nepenthes with a bootstrap value of 56. Clade II consists of species from the genus Nepenthes with a bootstrap value of 52. The results of this phylogenetic construction show the grouping of carnivorous plant species based on genetic similarity.